Prolonged Suppressive Effects of Periodontitis on Salivary TFF3 Production - Hormdee, Doosadee; Prajaneh, Saengsome; Kampichai, Amonrujee; Tak, Ranuch; Chaiyarit, Ponlatham (European Journal of Dentistry, 2019)
Objective As a follow-up to our previous study that demonstrated decreased salivary trefoil factor family 3 (TFF3) peptide levels in chronic periodontitis patients, this current study aimed to observe the effects of nonsurgical periodontal treatment on salivary TFF3 peptides in patients with periodontal diseases.Materials and Methods Eighty-seven volunteers that comprised of 30 individuals with healthy periodontium, 31 with gingivitis, and 26 with chronic periodontitis were considered for the study. Prior to periodontal treatment, a general periodontal examination was performed along with collection of saliva samples from each volunteer. Nonsurgical periodontal treatments were provided to patients with gingivitis and periodontitis. Two weeks post-treatment, saliva samples were recollected, and the periodontal status was re-evaluated. Salivary TFF3 concentrations were measured by enzyme-linked immunosorbent assay.Statistical Analysis Mann–Whitney U test was used when the investigated data were not normally distributed. Chi-squared test was used when dealing with categorical data. Kruskal–Wallis test with post-hoc corrections was used to compare data among the three investigated groups. Two-tailed p < 0.05 was considered as statistically significant.Results Prior to the periodontal treatment, salivary TFF3 concentrations in patients with gingivitis and periodontitis were significantly lower than those with healthy periodontium. Two weeks post-treatment, increased levels of salivary TFF3 were observed in patients with gingivitis, whereas the concentrations decreased in patients with chronic periodontitis.Conclusion This study demonstrated the effects of periodontal disease on the production of salivary TFF3 peptides. Interestingly, nonsurgical periodontal treatment also affected the recovery of salivary TFF3 peptides but varied in their outcomes between gingivitis and periodontitis patients.
Keywords: periodontal diseases; saliva; salivary glands; trefoil factor